2007
DOI: 10.1007/s00264-006-0297-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of freezing on the biomechanical and structural properties of human posterior tibial tendons

Abstract: This work analyzes the effects of storage by fresh-freezing at -80 degrees C on the histological, structural and biomechanical properties of the human posterior tibial tendon (PTT), used for ACL reconstruction. Twenty-two PTTs were harvested from eleven donors. For each donor one tendon was frozen at -80 degrees C and thawed in physiological solution at 37 degrees C, and the other was tested without freezing (control). Transmission electron microscopy (TEM), differential scanning calorimetry (DSC) and biomecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 31 publications
6
94
3
Order By: Relevance
“…The number of fibrils per unit area was decreased with cryopreservation. A similar observation was reported by Giannini et al (2008), who assessed the effect of storage by fresh-freezing at -80°C on human posterior tibial tendons. Tsuchida et al (1997) reported that collagen fiber bundles became separated into smaller bundles 3 weeks after in situ freezing of rabbit patellar tendon.…”
Section: Discussionsupporting
confidence: 69%
“…The number of fibrils per unit area was decreased with cryopreservation. A similar observation was reported by Giannini et al (2008), who assessed the effect of storage by fresh-freezing at -80°C on human posterior tibial tendons. Tsuchida et al (1997) reported that collagen fiber bundles became separated into smaller bundles 3 weeks after in situ freezing of rabbit patellar tendon.…”
Section: Discussionsupporting
confidence: 69%
“…4); more precisely, the RMSE was found inversely correlated with the freezing period (p = 0.039). Contradictory findings on the effects of freezing connective tissues have been reported in the literature (Clavert et al, 2001;Giannini et al, 2008;Viidik and Lewin, 1966;Woo et al, 1986); it is possible that freezing could affect the tendon's mechanical properties, especially since it can provoke tissue dehydratation and it was reported that SDFT water content is correlated to tendon SOS (Miles et al, 1996). In particular, fluid exudation in presence of higher water content might provoke a non-negligible mass loss during loading; the induced tissue density variations could affect the SOS, although the repeatability of the SOS/SRTM curves during load cycling undermines this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The repeated freeze-thaw protocol was designed to remove confounding biosynthetic contributions from endogenous tenocytes. Previous studies 46,47 reveal that freeze-thawing tendon does not alter the biomechanical properties of the tissue, suggesting that the collagenous matrix of tendon is not adversely affected by this procedure. However, it is possible that endogenous cellular debris might have influenced the activities of the exogenously administered cells.…”
Section: Discussionmentioning
confidence: 99%